Edge-enriched graphene with boron and nitrogen co-doping for enhanced oxygen reduction reaction - Kang, Gil-Seong; Lee, Sungho; Lee, Doh C.; Yoon, Chang Won; Joh, Han-Ik (ELSEVIER, 2020)
Carbon-based electrocatalysts for oxygen reduction reaction (ORR), especially in anion exchange membrane fuel cells (AEMFCs), have received a lot of attention because they exhibit excellent stability and are comparable to commercial Pt/C catalysts. Currently, to maximize the catalytic activity of carbon-based electrocatalysts, there are two major strategies: heteroatom doping or exposing active edge sites. However, the approach of increasing heteroatomic dopants of active edge sites has been rarely addressed. In this study, we present a simple strategy to prepare edge-enriched graphene catalysts with an increased ratio of heteroatomic dopants suitable for ORR of AEMFCs. The catalysts were prepared under harsh oxidation conditions, followed by a simple co-doping process with boron and nitrogen. The ORR activity of the catalysts was observed to be related to an increase of edge sites with heteroatomic dopants. We believe that the edge-enriched structure leads to accelerated electron transfer with enhanced oxygen adsorption.
Keywords: DOPED GRAPHENE; FREE CATALYSTS; OXIDE SHEETS; CARBON; ELECTROCATALYSTS; SIZE; PERFORMANCE; SULFUR; SITES